COMPLETE CROSS-SECTIONAL ANALYSIS OF HOTEL BUSINESS TERMS IN ENGLISH AND UZBEK LANGUAGES (World Bulletin of Social Sciences, 2024)
This article is about a complete cross-reference analysis of hotel business terms in English and Uzbek languages. In addition, the history of hospitality is the study of consumer and material and cultural services related to hospitality